A DIGE-based quantitative proteomic analysis of grape berry flesh development and ripening reveals key events in sugar and organic acid metabolism - Martínez Esteso, María José (2011)
Grapevine (Vitis vinifera L.) is an economically important fruit crop. The berry components that determine the final quality traits of both table and wine grapes, such as sugars, acids, flavours, anthocyanins, tannins, etc., are synthesized or accumulated along the different grape berry development stages. Thus, correlating the proteomic profiles with the biochemical and physiological changes known to occur in the grape berries along development is of paramount importance to advance in the understanding the ripening process. We report the developmental analysis of V. vinifera cv. Muscat d’Hamburg berries at protein level. We undertook a top-down proteomic approach based on differential in-gel electrophoresis (DIGE) followed by tandem mass spectrometry to determine differentially accumulated proteins. The green development (from fruit set to pre-veraison) and the ripening (from veraison to full ripening) were analysed as independent experiments. We have identified and quantified 154 and 61 deregulated proteins in green and ripening phases, respectively. Two key points in development at the protein change level have been determined: end of green development and beginning of ripening. An additional DIGE experiment was performed comparing fully ripe berries from two vintages in order to detect seasonal changes. As few spots changed we have concluded that protein changes detected in this study are developmental-specific. The role of amount of identified proteins is discussed in relation to grape berry development and to quality traits. The well known shift of imported sucrose fate at the beginning of ripening from accumulation of organic acid (malate) to hexoses (glucose and fructose) was well correlated with a switch between sucrose synthase and soluble acid invertase.